Hetero-interpenetrating porous coordination polymers. Issue 18 (26th April 2022) - Chang, Kai-Chi; Lee, Li-Wei; Lin, Hsiu-Mei; Yen, Chih-Feng; Wang, Chih-Min; Wu, Jing-Yun
Abstract : The interpenetration of porous coordination polymers is an appealing phenomenon; this Frontier article highlights hetero-IPCPs according to the structural features of individual networks involving the framework topology and chemical composition. Abstract : Interpenetrating porous coordination polymers (IPCPs) consist of two or more networks that are mechanically interlocked to form a coherent structure. The framework topology and the chemical composition are the two important criteria of interpenetrating networks to distinguish homo-IPCPs from hetero-IPCPs. Compared to rich homo-IPCPs, hetero-IPCPs remain rare and are formed rather unexpectedly. This Frontier article highlights hetero-IPCPs in accordance with the difference and/or identity of individual networks in terms of the framework topology and the chemical composition.